Congenital cobalamin malabsorption (Imerslund‐Gräsbeck syndrome) in two Beagles in the UK. Issue 1 (1st June 2015) - Murtagh, Kevin; Batchelor, Daniel; German, Alex; Piviani, Martina; Silvestrini, Paolo
Abstract : Two immature Beagles, one nine months old and one six months old, presented with a variety of clinical signs, including pyrexia, lethargy, weight loss and intermittent vomiting and diarrhoea in one Beagle and severe lethargy, haemorrhagic diarrhoea and vomiting in the second. Investigations in both cases demonstrated a serum cobalamin below the detection limit of the assay. Genetic testing confirmed a CUBN:c.786delC mutation in a homozygous state, confirming Imerslund‐Gräsbeck syndrome (IGS) in both Beagles. Both Beagles responded rapidly and completely to parenteral cobalamin supplementation. Both dogs are currently normal, receiving cobalamin subcutaneously every two weeks. This is the first report of genetically confirmed IGS in the Beagle breed in the UK.